Potency of Judicial Powers and Challenges of Independent Judiciary in Focus - Ogunlade, Femi; Aladejana, Tope (ABUAD Law Journal, 2025)
Law exists in a society to create rights and impose duties, the observance of which will make for a good society. However, the verdict of history has been that laws have not been observed to provide for orderliness. Essentially, this calls for an institution charged with responsibility of seeing that society’s laws are obeyed and of adjudicating over disputes resulting from non- observance or breach of these laws and of awarding redress. While we can neither appreciate nor advocate both in theory and in practice the complete independence of judiciary if we do not understand the extremely important role and power of this third arm of government, this paper examined the powers of the judiciary under the1999 Constitution of the Federal Republic of Nigeria (as altered). It further discussed the independence of the judiciary in our democratic system. While challenges of independent judiciary in our contemporary time were identified, useful recommendations are made to strengthen judiciary for the development of Nigeria’s economy.